2010
DOI: 10.1111/j.1540-627x.2010.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Education: Known Worlds and New Frontiers

Abstract: We explore three "worlds" that entrepreneurship educators generally teach in and introduce a new frontier where we discuss teaching entrepreneurship as a method. The method is a way of thinking and acting, built on a set of assumptions using a portfolio of techniques to create. It goes beyond understanding, knowing, and talking and requires using, applying, and acting. At the core of the method is the ability for students to practice entrepreneurship and we introduce a portfolio of practice-based pedagogies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
408
1
34

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 880 publications
(519 citation statements)
references
References 22 publications
6
408
1
34
Order By: Relevance
“…Isso converge com recomendações da literatura internacional (McCoshan, 2010;Neck & Greene, 2011;NIRAS Consultants, FORA, ECON Pöyry, 2008;Surlemont & Kearney, 2009). O atendimento dessas necessidades, tomadas separadamente ou, mais ainda, tomadas em conjunto, parece ser um projeto laborioso e de longo prazo, mas que conta com a predisposição e a demanda favoráveis dos estudantes quanto a melhorias da EE.…”
Section: Conclusõesunclassified
“…Isso converge com recomendações da literatura internacional (McCoshan, 2010;Neck & Greene, 2011;NIRAS Consultants, FORA, ECON Pöyry, 2008;Surlemont & Kearney, 2009). O atendimento dessas necessidades, tomadas separadamente ou, mais ainda, tomadas em conjunto, parece ser um projeto laborioso e de longo prazo, mas que conta com a predisposição e a demanda favoráveis dos estudantes quanto a melhorias da EE.…”
Section: Conclusõesunclassified
“…It is unacceptable to take anything for granted or to rely on the reports of others" (p. 233). The process of collecting field data with which to validate their business ideas is perhaps the single most effective way for students to build empathy for what it is like to be an entrepreneur, thus addressing Neck and Greene (2011) and Jones, Matlay and Maritz's (2012) calls.…”
Section: Inside-out Flip: Outside Of Classmentioning
confidence: 99%
“…Entrepreneurship education (EE) is argued to be a special case of education that requires experiential components for it to be effective (e.g, Rasmussen & Sørheim 2006;Haase & Lautenschläger 2011;Neck & Greene 2011;Rideout & Gray 2013;Mason & Arshed 2013). While the concepts are easy enough to comprehend, the real challenge resides in the 'teachability dilemma' (Haase & Lautenschläger 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Taatila (2010) found that relevant entrepreneurial skills and competencies are best learned through 'pragmatic real-life development projects' that are highly experiential in nature. Neck and Greene (2011) recommend that teaching entrepreneurship as a method which extends beyond understanding, knowing, and talking and requires using, applying and acting in an entrepreneurial manner is most effective.…”
Section: Moving Enterprise Education From the Zoo To The Junglementioning
confidence: 99%